2019
DOI: 10.1017/s1474748019000392
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing O-Minimal Groups in Tame Expansions of O-Minimal Structures

Abstract: We establish the first global results for groups definable in tame expansions of o-minimal structures. Let N be an expansion of an o-minimal structure M that admits a good dimension theory. The setting includes dense pairs of o-minimal structures, expansions of M by a Mann group, or by a subgroup of an elliptic curve, or a dense independent set. We prove: (1) a Weil's group chunk theorem that guarantees a definable group with an o-minimal group chunk is o-minimal, (2) a full characterization of those definable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In this section, we will show that in supersimple theories, all L H -definable groups in H-structures are definably isomorphic to L-definable groups. 4 We first introduce some basic notions and facts about H-structures developed in [2], as well as some results about groups in simple theories that we will use later.…”
Section: Groups In H-structuresmentioning
confidence: 99%
“…In this section, we will show that in supersimple theories, all L H -definable groups in H-structures are definably isomorphic to L-definable groups. 4 We first introduce some basic notions and facts about H-structures developed in [2], as well as some results about groups in simple theories that we will use later.…”
Section: Groups In H-structuresmentioning
confidence: 99%
“…In the supersimple SU-rank 1 case, Zou [22] has shown that groups definable in H-structures are definably isomorphic to type-definable groups in the base language. Similarly, Eleftheriou [13] has shown that any large group definable in a dense-codense expansion of an o-minimal theory is definable in the original theory.…”
Section: Introductionmentioning
confidence: 89%
“…Example 4. 13 Pseudofinite fields (see [14]). Assume U is a non-principal ultrafilter over N and let F = U F i be the corresponding ultraproduct (in particular it is ℵ…”
Section: Proposition 411 Let G Be a Definably Amenable Group Definable In M | T Such That Dim(g) = K And Let μ Be A Left-invariant Measurmentioning
confidence: 99%
See 1 more Smart Citation
“…By [5, Theorem 5.12] and Theorem 1.4 below, this strong structure theorem holds in many settings, among others when P is a dense prefixdcl‐independent set. In this last setting, the theorem has already been crucially used in applications, such as in the description of definable groups in trueM in [3], as well as in the point counting theorems in [4]. We expect that similar applications will soon be found in the rest of the settings of Theorem 1.4.…”
Section: Introductionmentioning
confidence: 93%